Theoretical models of separation selectivity for charged compounds in micellar electrokinetic chromatography - Puangpila,C. (Wiley-VCH Verlag, 2015)
Equations and theoretical models for MEKC separation selectivity (α MEKC) were established to explain a change in separation and electrophoretic mobility order of fully charged analytes, in which α MEKC is related to the dimensionless values of mobility selectivity in CZE (α CZE) and retention selectivity (α k) in MEKC, and where α CZE and α k are defined as the ratio of electrophoretic mobility in CZE and the ratio of retention factor (k) in MEKC for two charged analytes, respectively. Using four alkylparabens as test analytes, excellent agreement was found between the observed α MEKC and the proposed α MEKC models of test analytes in MEKC over a wide range of SDS concentrations and values of k. For example, in comparison with CZE separation of charged analytes, MEKC separation can enhance separation selectivity up to the maximum value when the selectivity ratio (ρ) is greater than 1.0 (ρ=α k/α CZE), while lower separation selectivity is obtained with ρ<1.0 (α CZE>α k>1). © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.